From modelling to management of project delivery: review on clash management process with BIM in Malaysia - Fawaz, Mustafa; Ibrahim, Rahinah; Rashidi, Ali; Abdul Ghafar, Maszura (Construction Research Institute of Malaysia (CREAM), 2021)
CITP 2016-2020 (Construction Industry Transformation Program) targets higher rate of implementation for Building Information Modelling (BIM). The Industrial Revolution (IR) 4.0 Roadmap for Construction Industry 2020-2025 further emphasizes the utilization of Building Information Modelling (BIM) and Industrialized Building Systems (IBS) to increase productivity in the Malaysian construction industry. One benefit of BIM is enhancing interactions between different team members and reducing the clashes since the design phase of an industrialized project. Despite all the efforts to avoid the construction clashes during design stage with the use of BIM models, there has been no ideal construction process with nil clashes. Hence, our study aims to identify the key areas where BIM could support the clash management process during a project’s lifecycle. The paper discusses about the clash management process, the barriers and challenges for BIM implementation, and the use of BIM technology for developing countries surrounding the BIM technology’s process, organizational stakeholders, and the BIM product. In reference to Malaysia, results include the extant of BIM impacts on the construction industry due to its restrictions during the design stage of the project. Results found alignment of BIM products to the management team’s actions during clash management process has potential to support BIM implementation and improve construction productivity, and thereby, reducing future reworks. Further studies are recommended to focus on automation in BIM technology during the construction stage specifically for improving in-situ clash management. This paper contributes to improving construction productivity and professionalism with BIM and industrialized building products to support IR 4.0 Roadmap for Construction Industry 2020- 2025 in Malaysia.